Solve -2*g - v - 3 = 0, g + v = 1 - 2 for g.
-2
Solve -7 + 5 = 2*p + 2*y, -y = 0 for p.
-1
Solve -2*c + 3*o - 7 = 0, 5*c + 5*o + 26 - 46 = 0 for c.
1
Solve 5*h - 3*u + 21 = 0, -14 - 3 = 3*h - 4*u for h.
-3
Solve 3*g + 15 = -4*b + b, -4*g + 4*b + 12 = 0 for g.
-1
Solve 4*f = 4*n, -4*n + 9 = -f - 0 for f.
3
Solve 0*o - 2*c = 3*o + 13, 5*c - 10 = o for o.
-5
Solve -j = 3*j + x + 11, 2*j = -2*x - 4 for j.
-3
Solve 15 = -a - 4*i, 4*a - 5 = 3*a + i for a.
1
Solve 2*r + 6*v - 7*v = 0, 3*r - 2*v - 2 = 0 for r.
-2